Lack of TSH stimulation in patients with differentiated thyroid cancer – possible causes - Gut, Paweł; Matysiak-Grześ, Magdalena; Fischbach, Jakub; Klimowicz, Aleksandra; Gryczyńska, Maria; Ruchała, Marek (Contemporary Oncology/Współczesna Onkologia, 2012)
Differentiated thyroid cancer is one of the most common endocrine cancers. Typical standard treatment includes total thyroidectomy with partial lymphadenectomy, then depending on the indications, treatment with iodine isotope 131-I. A prerequisite to conduct the therapy is to obtain endogenic thyroid-stimulating hormone (TSH) stimulation (TSH > 30 μU/ml). We describe two patients with differentiated thyroid carcinoma in whom no rise in serum TSH was observed after withdrawal of thyroxine. In one patient TSH deficiency was due to partial hypopituitarism secondary to a tumor of the pituitary gland. In the second patient the TSH level was suppressed by metabolically active thyroid tissue within bilateral ovarian teratomas. The problems with TSH growth after withdrawal of thyroxine requires additional studies to identify the cause. Above two possible reasons for the lack of TSH stimulation after withdrawal of thyroxine were presented. In the case of non-TSH stimulation due to hypopituitarism both control tests and isotope treatment should be carried out using stimulation by recombinant human TSH (rhTSH).